The extent of HIV-related stigma and the resultant discrimination among health care workers at Salvation Army Chikankata Mission Hospital, Mazabuka District, Zambia - Zachungnunga, Zairemthiama (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2012.